Clinical spectrum of contactin-associated protein 2 autoimmune encephalitis in children - Hu, Wenjing; Wang, Enhui; Fang, Hongjun; Li, Li; Yi, Jurong; Liu, Qingqing; Qing, Wei; Guo, Danni; Tan, Qianqian; Liao, Hongmei (Frontiers in Neuroscience, 2023)
Objective Anti-contactin-associated protein 2 (CASPR2)-related autoimmune encephalitis (AE) is more common in adults than in children. Clinical understanding of anti-CASPR2-antibody (Ab)-related AE, diagnosis and treatment standards are lacking in children. Therefore, this retrospective study on clinical symptoms and treatment outcomes in children with anti-CASPR2-Ab-related AE was conducted, to improve the clinical understanding of the disease, its diagnosis and treatment. Methods This study retrospectively assessed children with anti-CASPR2-Ab-related AE from January 1, 2020, to June 30, 2022, in the Department of Neurology at Hunan Children's Hospital. Data regarding demographics, clinical symptoms, laboratory examinations, electroencephalography (EEG), imaging, and curative were collected. Results Thirteen patients were positive for serum anti-CASPR2-Ab (age at manifestation, 25 months to 13 years old; median, 8.1 years old; male-to-female ratio, 8/5). One patient (P1) had dual Abs, including anti-CASPR2 and anti-N-methyl-D-aspartate receptor Abs; his symptoms were more severe than those of children with anti-CASPR2 Abs alone. The clinical symptoms of the 13 patients with anti-CASPR2 Ab were movement disorders (9/13), consciousness disorders (9/13), abnormal demeanor (8/13), seizures (7/13), language disorders (6/13), fever (6/13), pain (4/13), involuntary exercise (4/13), poor diet (4/13), vomiting (3/13), sleep disorders (3/13), mood disorders (3/13), eczema/itching/redness (2/13), sweating (P8), urinary disorders (P13), and cognitive disorders (P9). No tumors were found in any patient. Additionally, EEG results of six patients were abnormal and imaging findings such as abnormal signals were found in 10 patients. Moreover, all except one patient recovered well after treatment; P1 with overlapping syndrome underwent recovery for more than two years. None of the patients who recovered have had a relapse. Discussion and Conclusion Anti-CASPR2-Ab-related AE has several clinical manifestations. Anti-CASPR2-Ab levels were higher in male patients than in female patients. Moreover, related tumors are relatively rare. Most patients benefit from immunotherapy and have a lower chance of recurrence in the short term. Furthermore, different from patients who had anti-CASPR2-Ab AE alone, those with overlapping syndrome had a severe and complex condition requiring lengthy treatment and rehabilitation. Additional studies are needed to evaluate the long-term prognosis of these patients.